Estudo da toxicidade genética de efavirenz (EFV) e fumarato de tenofovir desoproxila (TDF) em células somáticas de drosophila melanogaster - Moraes Filho, Aroldo Vieira de (2013)
The antiretroviral drugs appeared to prevent the multiplying HIV virus in the body, reducing its virulence, but not eliminate it from infected cells. These drugs increase the length and the quality of life of AIDS patients. In this context, Efavirenz (EFV) is non-nucleoside reverse transcriptase inhibitors. The Tenofovir Disoproxil Fumarate (TDF), oral prodrug of tenofovir, is analogue of adenosine 5 'monophosphate, belonging to the class of nucleotide reverse transcriptase inhibitors. These drugs act on the mechanisms of HIV replication by inhibiting the action of reverse transcriptase and thus preventing viral DNA synthesis. In order to assess the toxic and toxic-genetic potential of EFV and TDF, the present study used the Test for Detection of Somatic Mutation and Recombination (SMART) in Drosophila melanogaster. 3rd stage larvae originating from standard cross (ST) between males mwh and females flr³, were treated with solution of EFV and TDF and distilled water (negative control), for approximately 48 hours (chronic treatment) until they reach the pupal stage. These strains are carriers of specific gene markers, located on the left arm of chromosome 3, which allow you to monitor events related to mutation, mitotic recombination and chromosome aberrations. The statistical diagnosis was obtained by conditional binomial test. In this work, the results demonstrated that the EFV was toxic in high concentrations, but showed no induction of toxic genetic events. Inversely, the TDF showed no toxicity at the concentrations tested, but was showed induction of toxic genetic events at all concentrations, with a prevalence of recombinogenic events. Then, it is essential to analyze constantly the effects risk/benefit of isolated drugs and identify toxic and toxic genetic activity of each drug in order to ensure the quality of life for patients who use monotherapies and offers support for investigations with therapies that use combinations of antiretroviral drugs.